A critical review of University of the Philippines Visayas (UPV) undergraduate research projects/theses in Political Science, 2000-2013. - Negrillo, Joseph Cordevilla (2014.)
The undergraduate research project is a critical review of the Political Science undergraduate Research Projects/Theses in Political Science, 2000-2013. The objects of the study summed up to 153 authored and co-authored undergraduate research projects/theses. The paper also aimed to analyze the trends and developments of thesis writing from 2000-2013 and determine whether thesis advisorship and socio-political and economic events in the local and national level do have bearing on the way UPV Political Science students write their undergraduate research projects. Furthermore, this research projects aimed to analyze the trends and developments of methodology and theories/ conceptual frameworks used by the author/s in designing their research project. A system of categorization was used to make the research more exclusive and independent of each other and to avoid overlapping with other theses. The major categories include (a) Electoral Politics and Political Elites in Local Politics, (b) On Governance of the Local (c) Political Culture, (d) Social Movements, Women Studies, and (f) Textual Analyses. The study concluded that the most research topics are inclined in the study of the state, political institutions, and political culture. Research methodology was predominantly inclined to empirical-positivist tradition given the undergraduate but only few did an ethnographic study. Lastly, Political Science theses are ?silent? to address the significant socio-economic and political issues that beset the country in a particular year. It is recommended the Political Science theses writers should critically reflect on the issues of the society and resonate it in their study to at least consider the level of social relevance of the study because Political Science will always be associated with the issues of the people and society at large.
Thesis (Undergraduate, Bachelor of Arts in Political - History) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo. 2014.
Keywords: Theses -- Political Sciences -- Research; Research Projects -- Plitical Sciences -- Research